Sentimental Twain - Camfield, Gregg (Univ. of Pennsylvania Press, 1994)
In Sentimental Twain, Gregg Camfield examines the major and minor works of Mark Twain to redraw the boundaries between sentimentalism and realism in the second half of the nineteenth century. Beginning by taking the reactions to the question of race in Adventures of Huckleberry Finn as a test case, Camfield reveals that sentimental ethics persist, though buried, in American culture, and he argues that Americans' ambivalent responses to sentimentalism explain some of the continuing controversy surrounding Mark Twain's work. Specifically, he contends, insofar as the liberal agenda remains substantially sentimental - especially when dealing with issues of race - today's readers of Twain participate in the same dialectic between sentimental compassion and realistic cynicism that Twain himself confronted. Camfield then traces the cultural development of this ethical dialectic and follows Mark Twain's reactions to it, showing that Twain was a closet sentimentalist whose public attacks on sentimentalism veiled a deep longing for a more compassionate world. Throughout, Sentimental Twain is grounded in a discussion of philosophical contexts of nineteenth-century American sentimental literature, paying particular attention to the Scottish Common Sense philosophers, but looking forward to the Pragmatism of William James.
Keywords: Twain; Mark <1835-1910>; Twain; Mark; Philosophie; Didactic fiction; American; Emotions in literature; Ethics in literature; Philosophy in literature; Sentimentalism in literature; Ethik; Realismus; Sentimentalität; Empfindsamkeit